Mother’s Knowledge Toward Stunting In Toddler - Moudy Muhaiminurrohima Putri; Wiwi Mardiah; Henny Yulianita (Journal of Nursing Care, 2021)
Indonesia ranks third highest in Southeast Asia after Timor Leste and India which have stunting problems with a prevalence of 27.67%. In West Java, especially in Pangandaran Regency in 2018, the prevalence of stunting was 1.2%. Increasing maternal knowledge about stunting can reduce the incidence of stunting. This study aims to identify a description of the knowledge of mothers with toddlers about stunting in Kalipucang Village, Pangandaran Regency. This research is used descriptive-quantitative by using primary data in the form of a questionnaire about stunting knowledge. The population of this study was 346 mothers of children under five in Kalipucang Village, Pangandaran Regency. The sample used was 186 samples with accidental sampling technique. The instrument used has been tested for validity and reliability and obtained r count > r table (n = 0.632) and cronbach’s alpha value of 0.896. The results of the study were analyzed by univariate analysis and then grouped into groups of respondents with good knowledge and poor knowledge. Based on data analysis, the results showed that more than half of mothers with toddlers in Kalipucang Village, Pangandaran Regency had a low level of knowledge, as many as 95 (51.1%) respondents. So, it is hoped that health services will improve health promotion in order to increase public knowledge regarding stunting.